2022
DOI: 10.3389/fpsyt.2022.820060
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Toward Psychiatry Among Medical Students With a Psychiatric Major at Chongqing Medical University

Abstract: ObjectivesTo understand the attitudes of medical students with a psychiatry major toward psychiatry at Chongqing medical university in China and to find out factors influencing students' career choice.MethodsThe present study used an online web survey tool to assess the attitudes toward psychiatry amongst 422 students majoring in psychiatry at Chongqing medical university in China using sociodemographic and Attitudes Toward Psychiatry-30 items (ATP-30) scales. Descriptive statistics and logistic regression ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
(53 reference statements)
0
1
1
Order By: Relevance
“…This proved our hypothesis wrong regarding the intention to become a psychiatrist during the recent period. These results are inconsistent compared with other related studies 17 , 18 . Although the fact that Q4 is the most difficult should make more sense, this was not always the case because a study revealed that the choice of a psychiatrist career is influenced by many factors, such as personality traits and characteristics, career aspects, stigma towards mental illness, student values and personal needs 2 , 8 , 19 .…”
Section: Discussioncontrasting
confidence: 79%
“…This proved our hypothesis wrong regarding the intention to become a psychiatrist during the recent period. These results are inconsistent compared with other related studies 17 , 18 . Although the fact that Q4 is the most difficult should make more sense, this was not always the case because a study revealed that the choice of a psychiatrist career is influenced by many factors, such as personality traits and characteristics, career aspects, stigma towards mental illness, student values and personal needs 2 , 8 , 19 .…”
Section: Discussioncontrasting
confidence: 79%
“…Compared with previous studies documenting negative attitudes toward psychiatry, what has changed over the years might be that various aspects of psychiatry have progressed and the field is rapidly expanding ( 4 , 48 , 55 ): accessible scientific evidence establishing psychotherapeutic treatments' effectiveness; the development of psychosomatic medicine applying to all medical diseases; improved quality of psychiatry teaching; growing prevalence of psychiatric diseases resulting in more exposure to the mentally-ill patients; and involvement with the acutely disturbed as well as successful cases of psychiatry may have exposed students to significance and advantages of psychiatry and challenged commonly held stigmatized view toward it.…”
Section: Discussionmentioning
confidence: 88%